Volume 1: Turbomachinery 1992
DOI: 10.1115/92-gt-030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Analysis of the Flow in a Centrifugal Compressor Volute

Abstract: Detailed measurements of the swirling flow in a centrifugal compressor volute with elliptical cross section are presented. They show important variations of the swirl- and throughflow velocity, total and static pressure distribution at the different volute cross sections and at the diffuser exit. The basic mechanisms defining the complex 3D flow structure are clarified. The different sources of pressure losses have been investigated and used to improve the prediction capability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This fact has been proved in many experiments reported in references (1) to (8). Two examples are given in Figs 2 and 3 (2, 3).…”
supporting
confidence: 67%
“…This fact has been proved in many experiments reported in references (1) to (8). Two examples are given in Figs 2 and 3 (2, 3).…”
supporting
confidence: 67%
“…Detailed measurements by Ayder et al indicated a very complex, threedimensional (3D) flow within the volute and gave fundamental insights for further research [2][3][4]. It is well known that the volute flow causes a rotationally non-symmetric pressure distribution in the diffuser outlet at off-design conditions: the volute acts as a diffuser at lower than design mass flow and as a nozzle at higher than design mass flow, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At large flow rates, the volute served as a nozzle and the flow inside the volute was accelerated in the circumferential direction; at low flow rates, the volute served as a diffuser and the flow inside the volute was diffused circumferentially. 2123…”
Section: Introductionmentioning
confidence: 99%